PERCEPTUAL ASSIMILATION OF STOPS BY CHINESE LEARNERS OF EUROPEAN PORTUGUESE - Oliveira, Diana (2019)
Perceiving and producing L2 oral stops is difficult for Chinese learners of European Portuguese (EP), namely the voicing distinction between these sounds (Shu 2014). The aim of the present study is to examine the degree of cross-linguistic similarity between the L1 and the L2 oral stops, in an attempt to shed light on the challenges Chinese learners of EP face when learning the L2 phonology (Batalha 1995; Martins 2008; Shu 2014).